Semiconductor laser diode control in optical disc writing systems. - Kosyak, I. V. (Інститут проблем реєстрації інформації НАН України, 2019)
An analysis of the principles of construction of control systems for semiconductor laser diode is carried out. Features of control of semiconductor laser for the system of recording optical disks are considered. The implementation of 405 nm wavelength semiconductor laser control device for recording Blu-ray, DVD, and CD formats is proposed.One of the main advantages of optical CDs, DVDs, and now Blu-Ray is the simplicity and low cost of replicating disks. Optical disk mastering is a key step in creating a stamp, of which ROM (read-only memory) disks are copied.The basis for the production of compact discs of any format is the laser recording stations, which provide relief recordings of original discs for optical memory, and are one of the most sophisticated modern optoelectronic systems.The Institute for Information Recording Problems of the National Academy of Sciences of Ukraine created the only working laser recording station in Ukraine. The urgent task remains to improve its work and research the new principles of its construction. This work is devoted to the analysis and research of the construction of a 405 nm wavelength semiconductor laser diode control device for recording systems for high density optical disks.When constructing a recording system for high-density optical discs, in particular CD, Blu-ray and DVD formats, there is a need for the development of a 405 nm wavelength semiconductor laser diode control unit that will provide the necessary modulation of laser radiation on CD, Blu-ray and DVD formats on laser recording station.The necessary control of the semiconductor laser diode is provided by circuit engineering methods and means. The radiation power of the semiconductor laser is clearly dependent on the current of the in the so-called active zone of its operation. Thus, the modulation of laser radiation is carried out by modulating the pump current. The schematic diagram of the developed device is constructed using analog and digital components.The main feature of the developed device is the presence of 3-channel control of the output power of laser radiation with the ability to adjust the reference current. This allows the use of different levels of power in the formation of channel coding impulses, which provides optimal forms and sizes of recordable pits for reliable reading of information from disks and use different recording materials for the original disk. Fig.: 6. Refs: 15 titles.